Negotiating Dutch citizen-led district heating projects: Managing internal, external, and material networks to achieve successful implementation - van der Schoor, Tineke; van der Windt, Henny J. (Energy research & social science, 2023)
Community energy can be conceptualized as a social movement, which aims to develop a sustainable, democratic, and localist energy system. Community energy organizations often take the form of cooperatives and strive for a high level of participation at the neighborhood level. Recently, community energy initiatives took on the challenge to develop neighborhood heating projects, which are citizen-led and sustainable. District heating (DH) projects are characterized by costly investments, a substantial overhaul of local infrastructure, and large installations for heat production. Furthermore, specialized technical knowledge is needed for the design of DH-systems. In the Netherlands, we studied four cases where local energy cooperatives developed such citizen-led neighborhood heating projects. Our primary research question is what constitutes a citizen-led or citizen-supported DH-project? We focus on four themes: first, the internal organization of the CH-project; second its outreach to local citizens; third, the role of technical knowledge and technology choices; fourth, the changing role of municipalities in the local energy transition. We developed a theoretical framework that consists of three main networks: the internal network, constituted by the local energy initiative itself and its surrounding neighborhood; the external network, which is comprised of local and regional governments as well as private companies; and the material network, referring to technological and physical aspects. In the discussion, we situate our findings against a broader European background. We conclude that a democratic structure, transparency of decision making, and a high level of activities to involve the neighborhood are key success factors. Nevertheless, the development of a community DH-project is a time-consuming process that takes a high toll on the participants. We observed that the remunicipalization trend is emerging in the Netherlands. Regarding technology choices, we found that the DH-initiatives became quite knowledgeable on technical issues and stimulated the application of new technologies such as small-scale aquathermal energy. However, in some cases the choice for a low-cost solution led to concessions to the sustainability of the proposed solutions.